1996
DOI: 10.1021/ja9602399
|View full text |Cite
|
Sign up to set email alerts
|

Zirconium(IV) Tetramer/Octamer Hydrolysis Equilibrium in Aqueous Hydrochloric Acid Solution

Abstract: Small-angle X-ray scattering measurements were performed on zirconium acidic aqueous solutions to investigate the structure and the size of polynuclear species larger than the previously identified tetrameric species. Solutions with [H+]added and [OH-]added ranging from 0.0 to 1.0 M and 0.0 to 0.02 M, respectively, were analyzed. This study demonstrates that an octameric species, Zr8(OH)20(H2O)24Cl12, exists in equilibrium with the tetrameric species, Zr4(OH)8(H2O)16Cl6 2+, such that, for 0.05 M Zr(IV) in high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
189
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(199 citation statements)
references
References 14 publications
10
189
0
Order By: Relevance
“…The literature reports indicated that at around pH 2.0, Zr(IV) exists as coordination complex of water {e.g. Zr8 (OH)20(H2O)24Cl12}, whose geometry has been determined to be octameric [20], and under similar conditions Hf(IV) has been reported to exhibit a similar chemistry [19]. These octameric species may be formed by bridging of two tetramers via four single OH -bridges and each metal cations of the octamer would bind to three H2O molecules.…”
Section: Results and Discussonmentioning
confidence: 99%
“…The literature reports indicated that at around pH 2.0, Zr(IV) exists as coordination complex of water {e.g. Zr8 (OH)20(H2O)24Cl12}, whose geometry has been determined to be octameric [20], and under similar conditions Hf(IV) has been reported to exhibit a similar chemistry [19]. These octameric species may be formed by bridging of two tetramers via four single OH -bridges and each metal cations of the octamer would bind to three H2O molecules.…”
Section: Results and Discussonmentioning
confidence: 99%
“…35 In the recent years, the compositions of the Zr(IV), Hf(IV) species in chloride media have been reported in several articles. [36][37][38] In the chloride medium, the only present zirconium and hafnium substance was reported to be partly hydrolyzed as [M 4 (OH) 8 -(H 2 O) 16 Cl 6 ]…”
Section: Resultsmentioning
confidence: 99%
“…Singhal et al 24 observed that there were tetramers and octamers of zirconium in acidic aqueous solutions using smallangle X-ray scattering (SAXS). In addition, unidentified polymeric species larger than the octamer were also formed under the condition when small amounts of NaOH were added.…”
Section: Aqueous Chemistrymentioning
confidence: 99%